High blood pressure and decreased heart rate variability in the Cuban epidemic neuropathy. Issue 1 (1st July 2002) - Gutierrez, J; Santiesteban, R; Garcia, H; Voustianiouk, A; Freeman, R; Kaufmann, H
Abstract : Autonomic cardiovascular reflexes were investigated in patients with an epidemic optic and peripheral neuropathy, which affected more than 50 000 people in Cuba between 1991 and 1994 and was probably caused by nutritional deficiency. Affected patients had significantly higher blood pressure than age matched controls, both while supine and standing, and significantly lower heart rate variability during paced breathing, suggesting reduced cardiac parasympathetic innervation.